KONTEKS SOSIAL DALAM TEKS SASTRA LISAN ANGNGARU GOWA (KAJIAN SOSIOLOGI SASTRA IAN WATT) - Darmawati, Darmawati; Hajrah, Hajrah; Faisal, Faisal (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
The study is the study of the text in Angngaru oral literature by using sociology of literature Ian watt as a scalpel. The aim of this study is to describe literature as a reflection of the social life of people in the oral literature text of Angngaru. The method in this study is qualitative descriptive. The data in this study is words, sentences, phrases found in the angtext. The data-gathering techniques in this study are reading and annotating techniques. The study involves identifying, decrypting, and analyzing literary texts that are viewed as reflecting public condition.Analysis shows that a number of oral literature texts of angngaru illustrate the courage and faithfulness of Kings and soldiers who could reflect the lives of gowa people in ancient times.